Polarization of Profit Sharing of Paddy Cultivation in the Acehnese Community as an Attempt to Alleviate Poverty: A Study of Fiqh Muamalah - Maulana, Muhammad; Amri, Aulil (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study examines the polarization of profit sharing in paddy cultivation in the tradition of the people of Aceh as an effort to alleviate poverty. This study, as the empirical or juridical sociological legal research, examines the behavior of law or operation of law in society. The study uses fiqh muamalah approach and obtains data through interviews and literature study. This study concludes that the pattern of profit sharing on the cultivation of paddy fields is categorized into a muzāra’ah aqd, which has rules specified in fiqh muamalah and promotes mutual assistance. However, traditionally, the people of West Aceh, Pidie, and Aceh Jaya utilizing leasing in managing paddy fields tend not to fully operate in accordance with the muzāra’ah aqd. This is due to the operational costs needed for the management of the fields have to be provided by the tenant farmers without financial contributions from the landowners at all. This method can easily allow the landowners to exploit the labor of tenant farmers as the tenants do not have other options aside from cultivating the land. As a result, tenant farmers find it difficult to get out of the shackles of poverty. Therefore, it takes effort to help the farmers out of poverty. It is expected that the government plays a role in the forms of the provision of aids such as seeds, fertilizers, medicines, harvesting machines, and rice threshers, with the goal to reduce expenditure costs of management and thus, the farming revenue will increase and farmers’ well-being will be achieved.